Explaining - Wragg, E. C. (Edward Conrad), 1938-; Brown, George (London ; New York : Routledge, 1993)
This book is about: Strategies of explanation; Analysing explanations; Knowing the subject matter; Effective explaining; ...
Keywords: Education; Teaching; Explanation; Teaching; Explanation